2012
DOI: 10.1007/s13187-012-0437-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Postgraduate Public Health and Biomedical Training Program Outcomes:

Abstract: To identify recent studies in the scientific literature that evaluated structured postgraduate public health and biomedical training programs and reported career outcomes among individual trainees. A comprehensive search of several databases was conducted to identify published studies in English between January 1995–January 2012 that evaluated career outcomes for trainees completing full-time public health or biomedical training programs of at least 12 months duration, with structured training offered on-site.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Published quantitative studies focused on defined postdoctoral training programs in the biomedical sciences are limited. A 2013 review identified only 13 studies with quantitative data published from 1995 to 2012 (e.g., scientific publications, grants, professional advancement) on career outcomes of former trainees in structured, full-time public health or biomedical postgraduate training programs of at least 12-month duration ( Faupel-Badger et al , 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Published quantitative studies focused on defined postdoctoral training programs in the biomedical sciences are limited. A 2013 review identified only 13 studies with quantitative data published from 1995 to 2012 (e.g., scientific publications, grants, professional advancement) on career outcomes of former trainees in structured, full-time public health or biomedical postgraduate training programs of at least 12-month duration ( Faupel-Badger et al , 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Step 5: Programme implementation, monitoring and evaluation (winter 2011 through spring 2014) Each priority health issue was treated over a 2-month period , including reading assignments, exercises and group work. The participation of students, their perception of the programme, their performance on assignments (formative and certifying examinations) and possible community outcomes were monitored throughout the curriculum with various techniques (automatic monitoring of connection to the platform [ 15 ]; strengths, weaknesses, opportunities and threats (SWOT) technique evaluation [ 18 ]; learning objective achievement [ 19 ]; outcome measurements [ 20 ]). Students completed a final individual examination and a collaborative report on specific transnational health issues with a focus on health workforce development as a final topic.…”
Section: Methodsmentioning
confidence: 99%
“…The participation of students, their perception of the programme, their performance on assignments (formative and certifying examinations) and possible community outcomes were monitored throughout the curriculum with various techniques (automatic monitoring of connection to the platform [ 15 ]; strengths, weaknesses, opportunities and threats (SWOT) technique evaluation [ 18 ]; learning objective achievement [ 19 ]; outcome measurements [ 20 ]).…”
Section: Methodsmentioning
confidence: 99%
“…The survey instrument was developed after conducting a literature search of training program evaluations to identify questions used in previous studies assessing postdoctoral training program outcomes [ 15 ]. Key themes and questions of interest to NCI, as well as input from previously conducted in-depth interviews of alumni [ 16 ] were incorporated into the development of the survey ( S1 File ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to determining the alignment of postdoctoral training with cancer prevention-related career outcomes, the rigorous evaluation design employed here may be of interest to the broader postdoctoral training community. To date, evaluations of structured, on-site postdoctoral training programs have been limited and have focused mostly on satisfaction measures [ 15 ]. Those evaluations reporting current employer or other career information have not included a comparison group to provide additional context for understanding the added value of the training program.…”
Section: Introductionmentioning
confidence: 99%